THE ANALYSIS OF SERVICE QUALITY, INNOVATION, AND CORPORATE IMAGE ON CUSTOMER LOYALTY OF RAGEY VON VON RESTAURANT - Mongdong, Meidy Angel (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
People always get hungry so they need food and people find themselves hungry with no time to cook, so they eat out. That’s why booming the restaurant industry. The restaurant business in North Sulawesi especially in Tomohon have been growing rapidly, particulary minahasa restaurant that selling typical local food Tomohon or Manado because the majority is Christian people therefore many restaurant selling Minahasa food. Service quality, innovation and corporate image is very supportive of customer behavior, especially customer loyalty at Ragey VonVon restaurant. Ragey VonVon restaurant toward the service quality, innovation, and corporate image on customer loyalty. This research used primary and secondary data. The method used to analyze the data is the Multiple Regression Analysis. The population in this study is a customers of Ragey VonVon restaurant where as samples taken by each respondent 100 respondents. This study reveals that service quality, innovation, and corporate image has significant effect partially on customer loyalty in Ragey Von Von. Therefore, Service quality, innovation, and corporate image very influence toward customer loyalty that has been one of the most important keys to the restaurant success. of Ragey Von Von restaurant must consider about the importance of service quality, innovation and corporate image, regarding with it in advanced. Keywords: service quality, innovation, corporate image, customer loyalty